The Influence Of Operating Expenses To Operating Income Ratio (BOPO) And Loan To Deposit Ratio (LDR) On Non Performing Loan (NPL) At Pt Bank Pan Indonesia Tbk For The Period 2015-2024 - Zaiparna, Syachel Muzaqi; Fadli, Achmad Agus Yasin (Jurnal Fokus Manajemen, 2025)
The purpose of this research is to determine the effect of the Operational Cost of Operating Income (BOPO) and the Loan to Deposit Ratio (LDR) on Non-Performing Loans (NPL) at PT Bank Pan Indonesia Tbk for the period 2015-2024, both partially and simultaneously. The method used is the Quantitative Method. The sample used is the income statement and balance sheet of PT Bank Pan Indonesia Tbk for the period 2015-2024. Data analysis is performed using descriptive statistical tests, classical assumption tests, multiple regression analysis, hypothesis tests, and coefficient of determination tests. The results of the study show that partially, the Operational Cost of Operating Income (BOPO) has a significant effect on Non-Performing Loans (NPL) with a significance value of 0.005 < 0.5 and a t-value of 3.990 > t-table 2.365. The Loan to Deposit Ratio (LDR) does not have a significant effect on Non-Performing Loans (NPL) with a significance value of 0.216 > 0.05 and a t-value of 1.361 > t-table 2.365. The results of the simultaneous test of Operational Costs to Operational Income (BOPO) and Loan to Deposit Ratio (LDR) have a positive and significant effect on Non-Performing Loans (NPL) with a significance value of 0.015 < 0.05 and calculated F value of 8.099 > table F value of 4.74. The results of the Coefficient of Determination test show R Square of 0.698 or 69.8%, which means that together the influence of Operational Costs to Operational Income (BOPO) and Loan to Deposit Ratio (LDR) on Non-Performing Loans (NPL) contributes 69.8%, while 30.2% is influenced by other variables outside this research model.